Research progress in the treatment of chronic primary immune thrombocytopenia - HUANG Zhouxuan; SHAO Jingbo (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Primary immune thrombocytopenia (ITP) is an acquired autoimmune disease characterized by isolated thrombocytopenia resulting from increased platelet destruction and impaired platelet production. Although the majority of patients have a relatively good prognosis, 10%‒20% of children and up to 75% of adults may progress to chronic primary immune thrombocytopenia (CITP). These patients exhibit poor response to multiple therapies, leading to a significant decline in quality of life. At present, the treatment strategies for CITP mainly include first-line therapies such as glucocorticoids and gamma globulin, and second-line therapies such as thrombopoietin receptor agonists (TPO-RAs), rituximab, immunosuppressants, and splenectomy. In recent years, with the in-depth research on CITP, some new biological drugs and immunotherapies, such as Fcγ receptor (FcγR) signal transduction inhibitors, neonatal Fc receptor inhibitors, complement inhibitors, immune-cell-targeted therapies, platelet desialylation, umbilical cord mesenchymal stem cell therapy, and chimeric antigen receptor T cell immunotherapy, have shown good therapeutic potential. By targeting specific pathways in the pathogenesis of CITP, these novel therapies aim to achieve individualized precision treatment, thereby providing patients with more effective therapeutic options. This article reviews the pathogenesis, second-line treatment approaches, and therapeutic advances in CITP.